Estimation of Labour Supply in New Zealand - Joseph Mercante; Penny Mok (New Zealand Government, The Treasury, 2014)
In this paper we estimate labour supply using a discrete choice approach for single men, single women and single parents and a joint labour supply equation for couples in New Zealand. The data are based on pooled cross-sectional data from the Household Economic Survey over 2006/07 to 2010/11. We allow singles to choose from eleven discrete hours whilst couples choose from 66 combined working hour choices. Net incomes at all possible discrete working-hours are calculated using Treasury's TAXWELL microsimulation model. For non-workers, net incomes are estimated based on an imputed wage. In order to fit the model to the observed working hour distribution we include a fixed cost of working parameter and we explicitly take account of observed and unobserved heterogeneity in the data. We find that the coefficient estimates of the labour supply equations mostly accord with expectations and are reasonably comparable with previously estimated equations for New Zealand. Using the equations we find that the labour supply predictions fit the observed data reasonably well. However, despite the inclusion of a fixed cost of working parameter, the peak working hours of around 40 hours per week in the observed data is under-predicted by the models, while part-time hours of work remain over-predicted. We compute labour supply elasticities from the estimated parameters which show that single parents and single women are the most responsive, whilst partnered men and single men are the least responsive.
Keywords: C25; J22; 330; labour supply; discrete choice; random utility; multinomial logit; Arbeitsangebot; Diskrete Entscheidung; Geschlecht; Eltern; Logit-Modell; Schätzung; Neuseeland